MEASURES TO COMBAT INFECTIOUS DISEASES (VIRAL HEPATITIS) IN UZBEKISTAN AND ITS RESULTS (EXAMPLE OF 1950-1980) - Gavhar Mominova (Journal Park Publishing, 2023)
In this article, the spread of infectious diseases is based on a number of natural conditions, the essence of the state's socio-economic policy, in particular, the material life of the population, the government's policy in the field of health care, the extent of the spread of sanitary knowledge among the population, residential areas, the sanitary condition of cities and districts, the close connection with such issues as environment and ecology, supply of clean drinking water, food consumption level of the population has been reflected.
Keywords: infectious disease, hepatitis, viral, jaundice, epidemic, special hospital, treatment.